Urinary tract infection in children with congenital anomalies of the kidney and urinary tract attending the division of paediatric nephrology at Charlotte Maxeke Johannesburg academic hospital, South Africa - Okoronkwo, Nneka Chioma (My University, 2016)
Background: Both CAKUT and UTI can independently cause renal insufficiency with ultimate progression to ESRD, and CAKUT is a well-documented risk factor for UTI in children. Aim: To describe CAKUT in a cohort of children, between 2 weeks and 18 years of age, and to document the patterns of UTI in this group. Method: A retrospective medical record review was performed on all patients with documented CAKUT managed between January 2005 and December 2014. Results: The prevalence of CAKUT was 20% and the male: female ratio was 4.4:1. The median age at presentation was 8.4 months and the median duration of follow up was 39 months. At presentation 57% were under the age of one year and 21% were above the age of 5 years. PUV was the commonest type of CAKUT and a very low rate of VUR was noted. The incidence of UTI was 41.8% and the odds of getting a UTI were significantly increased among children with bladder anomalies, PUV and collecting system anomalies. Escherichia coli and Klebsiella pneumonia were the commonest bacteria isolated and, although more than 90% of both E. coli and Klebsiella pneumoniae were sensitive to amikacin, meropenem, imipenem and ertapenem, more than 40% were resistant to commonly used oral antibiotics such as amoxicillin/clavulanate and trimethoprim-sulphamethoxazole. Prophylactic antibiotic use was highest among patients with PUV (35%) and, overall, patients who were not on a prophylactic antibiotic were five times more likely to have a UTI. The association between antibiotic prophylaxis and the development of antibiotic resistance could not be explored but there was a statistically significant association between the type of bacteria isolated and the use of antibiotic prophylaxis. Conclusion: Delayed presentation, the high rate of UTI and the high rate of antibiotic resistance to many first line oral antibiotics are all of concern. The study highlights the effectiveness of antibiotic prophylaxis in this group. Future research topics include determining the long term outcome, and the long term effects of antibiotic prophylaxis on renal function, in our cohort.
Dissertation submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Medicine Johannesburg, 2016